Pandangan Islam Tentang Kelompok dalam BK - Regita Amira Putri; Ahmad Syarqawi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study is in the form of a library research literature study, using a descriptive qualitative study method, while the approach used in this research is content analysis. The thing discussed is the Islamic view of groups in guidance and counseling.